Reactive spinal glia convert 2-AG to prostaglandins to drive aberrant astroglial calcium signaling - Dócs, Klaudia; Balázs, Anita; Papp, Ildikó; Szücs, Peter; Hegyi, Zoltán (Frontiers in Cellular Neuroscience, 2024)
The endogenous cannabinoid 2-arachidonoylglycerol (2-AG) influences neurotransmission in the central nervous system mainly by activating type 1 cannabinoid receptor (CB1). Following its release, 2-AG is broken down by hydrolases to yield arachidonic acid, which may subsequently be metabolized by cyclooxygenase-2 (COX-2). COX-2 converts arachidonic acid and also 2-AG into prostanoids, well-known inflammatory and pro-nociceptive mediators.Here, using immunohistochemical and biochemical methods and pharmacological manipulations, we found that reactive spinal astrocytes and microglia increase the expression of COX-2 and the production of prostaglandin E2 when exposed to 2-AG. Both 2-AG and PGE2 evoke calcium transients in spinal astrocytes, but PGE2 showed 30% more efficacy and 55 times more potency than 2-AG. Unstimulated spinal dorsal horn astrocytes responded to 2-AG with calcium transients mainly through the activation of CB1. 2-AG induced exaggerated calcium transients in reactive astrocytes, but this increase in the frequency and area under the curve of calcium signals was only partially dependent on CB1. Instead, aberrant calcium transients were almost completely abolished by COX-2 inhibition. Our results suggest that both reactive spinal astrocytes and microglia perform an endocannabinoid-prostanoid switch to produce PGE2 at the expense of 2-AG. PGE2 in turn is responsible for the induction of aberrant astroglial calcium signals which, together with PGE2 production may play role in the development and maintenance of spinal neuroinflammation-associated disturbances such as central sensitization.